FEASIBILITY OF ANIMATION LEARNING MEDIA USING ADOBE ANIMATE IN CHILD DEVELOPMENTAL PSYCHOLOGY TRAINING SUBJECTS - Timbul Sasongko; sri marmoah; Moh. Salimi (SOSIOEDUKASI, 2026)
This is an open The understanding of child developmental psychology is crucial for the pedagogical competence of elementary school teachers; however, the reality on the ground shows that teachers’ access to practical, interactive learning materials that support self-directed learning remains limited. The purpose of this study is to analyze the feasibility of using Adobe Animate animation media in child developmental psychology training courses to enhance pedagogical competence as a self-directed learning tool for elementary school teachers. This study is a Research and Development (R&D) project. The development procedure for this learning media consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The results of this study, as assessed for media feasibility, indicate that the media expert scored it at 227 (very high/A category), the language expert at 59 (very high/A category), the content expert at 64 (very high/A category), and the instructor scored the visual aspect at 44 (very high/A category) and 53 for content (very high/A category). A limited group of trainees scored 212 for presentation (very high/A category) and 259 for content (very high/A category), while a broader group of trainees scored 427 for presentation (very high/A category) and 517 for content (very high/A category)